2020
DOI: 10.1016/j.jvs.2020.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Experience from a Singapore tertiary hospital with restructuring of a vascular surgery practice in response to national and institutional policies during the COVID-19 pandemic

Abstract: Singapore was one of the first countries to be affected by COVID-19, with the index patient diagnosed on January 23, 2020. For 2 weeks in February, we had the highest number of COVID-19 cases behind China. In this article, we summarize the key national and institutional policies that were implemented in response to COVID-19. We also describe in detail, with relevant data, how our vascular surgery practice has changed because of these policies and COVID-19. We show that with a segregated team model, the vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
0
18
0
3
Order By: Relevance
“…Similar COVID-19–driven practice restructuring has been reported from a tertiary hospital in Singapore. 11 The present guideline although fundamentally in line with these previously published principles is based on the unique situation in Bangladesh. We have taken into account the availability of not only vascular surgeons but also the supporting staff including anesthesiologists and those who have access to the OT and catheterization laboratories.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar COVID-19–driven practice restructuring has been reported from a tertiary hospital in Singapore. 11 The present guideline although fundamentally in line with these previously published principles is based on the unique situation in Bangladesh. We have taken into account the availability of not only vascular surgeons but also the supporting staff including anesthesiologists and those who have access to the OT and catheterization laboratories.…”
Section: Discussionmentioning
confidence: 77%
“…The previously mentioned strategy is fundamentally different from that pursued in the developed countries. 10 , 11 Realizing the pitfalls of this strategy, the government of Bangladesh has now changed its policy to accommodate patients both with COVID-19 and without COVID-19 in the same facility. 12 However, it is still not clear how effective this will be in delivering patient care without compromising safety.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 19 articles had reported changes in the conduct of emergency and elective VS cases in respective institutions. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 In summary, all articles reported continuation of emergency VS cases such as ruptured AAAs, and deferment of non-urgent elective VS cases such as revascularization for claudicants and varicose veins. There was some inter-institutional variation between the type of VS cases that proceeded or were deferred.…”
Section: Resultsmentioning
confidence: 95%
“… 26 Ng JJ et al had also reported an increase in major amputation rates from 2.5% of all VS cases performed in November and December 2019 combined, to 4.2% of all VS cases performed in January to March 2020 combined. 37 Boschetti GA and Mascia D et al both reported more patients presenting late with limb ischaemia. 23 , 27 Lastly, Bashar AHM et al similarly reported a decrease in limb salvage rate from 83.6% to 72.4% for patients presenting with CLTI during the COVID-19 pandemic compared to a pre-pandemic period.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation